Effect of Weed-Control Measures on Yield, Weed Control, Economics, Energetics and Soil Microflora under Different Establishment Methods of Wheat (Triticum aestivum L.) - Sirazuddin; Singh, S. P.; Singh, V. P.; Mahapatra, B. S.; Verma, Himanshu (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted during rabi season of 2013-2014 at Pantnagar, District, Udham Singh Nagar (Uttarakhand) to assess the effect of weed-control measures on grain yield, weed control efficiency (WCE), economics, energetic and soil microflora of wheat (Triticum aestivum L.) under different establishment methods. The highest grain (4688 kg ha-1) and biological yield (12131 kg ha-1) was obtained in the plots treated with clodinafop-propargyl @ 60 g ha-1. Grain and biological yield loss under RTW, CTW and ZTW due to weeds was 75.9% and 30.8%, 22.3% and 11.5% and 18.3% and 14.3%, respectively. Ready mix of clodinafop-propargyl+MSM @ 64 g ha-1 in each establishment method of wheat recorded 100% weed control efficiency at 60, 90 DAS and at maturity. Highest B: C ratio (2.5) was achieved under clodinafop-propargyl @ 60 g ha-1 which was at par with ready mix of clodinafop-propargyl+MSM @ 64 g ha-1. Maximum energy input (15717 MJ ha-1) was recorded under CTW with two hand weedings and the lowest energy input (15113 MJ ha-1) was recorded under RTW in weedy plot which was closely followed by weedy plots of ZTW. Energy output (171483 MJ ha-1), net energy return (156354 MJ ha-1) and energy use efficiency (11.3) was maximum in case of RTW plots where ready mix of clodinafop-propargyl+MSM @ 64 gha-1 was applied. Energy intensity (3.0) was lowest under RTW with clodinafop-propargyl @ 60 g ha-1. The lowest population of bacteria (6.87 log cfu) and actinomycetes (5.46 log cfu) was recorded under ready mix of clodinafop-propargyl+MSM @ 64 g ha-1.